Komunikasi Politik Penggunaan Media Sosial dalam Komunikasi Politik Generasi Z pada Pemilihan Bupati Pangandaran 2024 - Dalfa Amalia; Evie Ariadne Shinta Dewi; Samson CMS (KOMVERSAL, 2025)
The change in political communication patterns has changed significantly by utilizing social media as a medium for delivering political communication, generation Z is also a generation that will take over the face of Indonesian politics in the next few years, currently most of generation Z are also new voters and on the other hand generation Z is also very connected to digital technology. The purpose of this study is to determine the role of social media for generation Z in Pangandaran in the 2024 Pangandaran regent election activities, to find out why generation Z chooses social media as a source of information about the regent election and to find out what political communication models are formed through Generation Z interactions on social media during the 2024 Pangandaran regent election. This study uses a qualitative research method through a case study approach. The results of this study indicate that social media plays a role as the main source of information, political socialization agent for voting decisions, popular media, interactive and designing political communication strategies. The reason generation Z chooses social media is because of its flexible and easily accessible nature, easy-to-understand messages, diverse and interesting information references. While the political communication model that is formed is a transactional political communication model.